Website sobre planejamento das cirurgias do contorno corporal em pacientes pós-bariátricos - Abrile, Gustavo Gualberto [UNIFESP] (2020)
Introduction: Over the past few years, there has been an increasing number of bariatric surgeries, and in this sense, an increase in the demand for Plastic Surgery to improve body contour. The post-bariatric patient has distinct clinical and laboratory characteristics, resulting in greater attention from plastic surgeons to provide quality preoperative planning. Objective: To develop a digital platform (website) for planning body contour surgery in post-bariatric patients. Method: The Design Thinking methodology was used and followed the four stages of Double Diamond: I. “Discover”: Desk research through the search of the literature covering the period from January 2010 to June 2020 in the databases. And Internet sites. Closed questionnaires were conducted based on the literature and sent online to plastic surgeons, II. “Define” in association with an Information Technology professional. III. “Develop” its content and layout and, finally, IV. "Deliver" the website. Results: The themes and content for creating the website were based on the results of searches on databases, research sites and responses to the questionnaires sent to experienced surgeons. It was defined that the product of the present study could: guide plastic surgeons in preparing post-bariatric patients to undergo body contouring procedures; prepare a complete and easy-to-read content to optimize comprehensive care for post-bariatric patients; present specific categorizations named as: Initial assessment (anamnesis, physical examination and photographic documentation); Nutritional assessment; Skeletal evaluation; Psychological assessment, and; General recommendations Conclusion: a website was developed to assist plastic surgeons in scheduling surgeries for body contouring in post-bariatric patients, available at www.planejamentoposbariatrico.com